Adoptive therapy for EBV-induced cancers: driving success with post-transplant lymphoproliferative disorder to other EBV-derived tumors. (May 2015) - Smith, Corey; Khanna, Rajiv
Epstein–Barr virus (EBV) infection is associated with a range of human malignancies of lymphocytic and epithelial cell origin. In addition to viral-mediated and genetic oncogenic events that lead to the establishment of EBV-associated malignancies, defects in the immune control of EBV likely play a significant role in promoting the survival of malignant cells. This breakdown in immune surveillance is most evident in immunocompromised transplant patients who are susceptible to the development of post-transplant lymphoproliferative disorders. Observations over the last two decades have shown that reconstitution of EBV-specific cellular immunity via adoptive cell therapy can have a dramatic effect on both preventing and treating post-transplant lymphoproliferative disorders, leading to hope that similar strategies could be effective in preventing more prevalent EBV-associated malignancies.